Measuring teacher competency for the era of education 4.0 in Malaysian secondary schools / Mei Kin Tai, Musa Khalip and Abdull Kareem Omar - Mei, Kin Tai; Khalip, Musa; Omar, Abdull Kareem (Universiti Teknologi MARA, 2022)
The main purpose of the study was to measure the level of teacher competency for the era of Education 4.0 (TCEdu4.0) in Malaysian secondary schools. The study employed a quantitative approach with a total of 1,078 teachers completing the survey. Descriptive statistics were applied for data analysis. The results revealed that, i) teachers achieved Quite Good level in the practice of TCEdu4.0 and its six dimensions; ii) among the six competencies of TCEdu4.0, teachers achieved the highest mean score in Pedagogical Psychology and Assessment but obtained the lowest mean score in Functional and Research Competency; and iii) teachers achieved at the upper level of Quite Good in Pedagogical Psychology and Assessment, Self-Management and Interactive Competency, and Problem Solving but at a lower level of Quite Good in Technological and Digital Competency, Leading Learning and Mentoring and Functional and Research Competency. The study summarised that only professional development programmes that are teacher-driven can empower teachers to take ownership of their learning experiences as they recognise teachers as professionals with valuable insights for teachers’ continual growth. The study offers one small step in the direction of continuous teacher development and growth in the face of the FIR both locally and internationally.